Application of the Apriori Algorithm in Transaction Data in Rumah Makan Murah - Marthy, Nicola; Tundo, Tundo; Nabilah, Laila; Maharani, Delia (Edusight International Journal of Multidisciplinary Studies, 2024)
This research aims to apply the Apriori algorithm in transaction data analysis at a budget-friendly restaurant to identify purchasing patterns and relationships between frequently bought items. By leveraging historical transaction data, the Apriori algorithm can discover significant associations among various menu items, which can then be used to develop more effective marketing strategies, optimize product placement, and boost sales. The research process includes the collection and preprocessing of transaction data, application of the Apriori algorithm for association rule extraction, and analysis and interpretation of the results. The findings from this study are expected to provide valuable insights for budget-friendly restaurant managers to develop more efficient, data-driven business strategies.